A comparative study of the structure and bonding in heavier pnictinidene complexes [(ArE)M(CO)n] (E = As, Sb and Bi; M = Cr, Mo, W and Fe). Issue 11 (27th February 2017) - Vránová, Iva; Kremláček, Vít; Erben, Milan; Turek, Jan; Jambor, Roman; Růžička, Aleš; Alonso, Mercedes; Dostál, Libor
Abstract : A comprehensive study on the coordination behaviour of rare examples of heavier monomeric pnictinidenes is presented. Abstract : N, C, N -Chelated pnictinidenes ArE [where E = As (1 ), Sb (2 ) or Bi (3 ); Ar = C6 H3 -2, 6-(CHN t -Bu)2 ] were used as ligands for the coordination of transition metal carbonyls. Thus, the reaction of1–3 with [M(CO)5 THF] (where M = Cr, W) or [Mo(CO)5 (Me3 N)] gave complexes [(ArE)M(CO)5 ] [where E = As and M = Cr (1a ), Mo (1b ), W (1c ); E = Sb and M = Cr (2a ), Mo (2b ), W (2c ); E = Bi and M = Cr (3a ), Mo (3b ), W (3c )]. Analogously, the treatment of1–3 with [Fe2 (CO)9 ] resulted in the formation of the complexes [(ArE)Fe(CO)4 ] [where E = As (1d ), Sb (2d ) or Bi (3d )]. All compounds were characterized by 1 H and 13 C NMR spectroscopy, Raman, IR and UV-Vis spectroscopy. The molecular structures of the majority of the compounds (except1b and1c ) were also determined by the single-crystal X-ray diffraction analysis. Furthermore, the structure and bonding of the title compounds have also been thoroughly investigated using a computational approach.